English validation of the Multidimensional Scale of Motives for Postponing Parenthood (MSMPP-18-EN): Factorial structure, psychometric properties, and correlates - Małgorzata Szcześniak; Adam Falewicz; Marianna Chmiel; Zdzisław Kroplewski (PLoS ONE, 2025)
Introduction While the literature on deferred parenthood is rich in analyses of this topic from a sociological and medical point of view, psychological research is in the minority. The analysis also shows that there are no questionnaires to measure motives for postponing parenthood. This gap is filled by the Multidimensional Scale of Motives for Postponing Parenthood (MSMPP-18) which assesses the motivational forces that may lead to the decision to postpone parenthood. Given that most studies and articles on deferred parenthood are reported in English, the two main goals of Studies 1–3 reported in the present research were to: 1) validate the original Polish version of the MSMPP-18 into English; 2) confirm its convergent validity. Methods The original version of the MSMPP-18 was translated into English by two independent psychologists fluent in academic English using a traditional forward-backward translation technique. The factorial structure of the MSMPP-18-EN and its psychometric characteristics were verified through Confirmatory Factor Analysis (CFA). The criterion validity of the scale was examined using the correlation between the motives for postponing parenthood and a nomological set of variables in Studies 1–3 (total N = 664; n1 = 247; n2 = 239; n3 = 178). Results The CFA statistics provided empirical evidence that the MSMPP-18-EN has good fit indices across Studies 1–3, both for the first-order model and the second-order model. The research confirmed that the English-language version of the scale reveals factors analogous to the original scale: 1) feeling of uncertainty and incompetence; 2) self-focus; 3) parenthood as a burden; 4) fear of change; 5) financial security concerns; and 6) worry about a child’s future. The values of Cronbach’s alpha (Studies 1–3: 0.75–0.95; 0.68–0.93; 0.77–0.93), McDonald’s Omega (Studies 1–3: 0.76–0.96; 0.73–0.93; 0.79–0.93), and CR (Studies 1–3: 0.89–0.97; 0.80–0.99; 0.78–0.99) displayed good internal reliability. Data from Studies 1–3 also showed that procrastination, future anxiety, need for closure, negative emotions toward God, and family disfunction positively and significantly correlated with motives for delayed parenthood and its overall score. On the other hand, motives of postponed parenthood were negatively and significantly correlated with psychological capital, social support, positive emotions toward God, life satisfaction, self-efficacy, and self-regulation. Conclusions The presented validation of what is probably the first scale measuring the motives for deferred parenthood allows us to assume that the MSMPP-18-EN tool in the English version meets the theoretical and empirical criteria of a good questionnaire.